A STUDY OF THE TRANSLATION OF ENGLISH ADVERBS OF MANNER INTO INDONESIAN FOUND IN DAVID NICHOLLS' ONE DAY - Nollan Dayna Susie Chrismalia Garnida (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This article reports a study on the problem of non-equivalence in the Indonesian translation of English adverbs of manner at word level. The aim of this study is to examine the translation of English adverbs of manner for SL (English) into TL (Indonesian) with Mona Baker’s strategy of translation as the theoretical framework. The qualitative descriptive research design is adopted in the study. The data source is David Nicholls’ novel One Day (2009) and its Indonesian translation (2012). The study involved 118 data. Of these,  seventy-seven (77) data are showing equivalence, and forty-one (41) data non-equivalence. As expected, the equivalent data are translated into the word or phrase structure of ber-, se+Adj 2x+ nya, se+Adj+N, per-, dengan+Adj, suffix –nya in the TL text. The focus of analysis is in the non-equivalent data. Two strategies were found:  (1) translation by mission and (2) translation by a more neutral word. The reasons for the omission of the adverbs of manner include: the TL texts have already use other words with similar meaning, sufficient information without their mention, the context has made it clear. The reasons for the second strategy include avoidance of awkward meaning and building a more neutral sense.